No man an island : the cinema of Hou Hsiao-Hsien - Udden, James (Hong Kong University Press, 2017)
This is a book-length study of Hou Hsiao-Hsien, Taiwan's famous director of movies such as 'The Puppetmaster', 'City of Sadness', 'Flowers of Shanghai', and 'Goodbye South, Goodbye'. His body of work reflects a unique film style chracterized by intricate lighting, improvisational acting, and long, static shots.